Aplikasi Penginderaan Jauh Untuk Penentuan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The objective of this research is to determine the geothermal potential dissemination area using Remote Sensing. This study took place in kamojang Region, Bandung Regency and garut Regency, West Java Province. The research method used is digital data analysis of image Landsat TM b doing, a contrast stretching technique, spatial Filtering and color composite image to interpret visually the lineament. The determination of the geothermal potential dissemination area uses an overlaying technique from the three thematic maps, i.e., lineament density map, reservoir isothermal map, map and resistivity map, which each mapping unit is given a score. The geothermal potential dissemination falls into three areas, i.e., are high potential area (233,054 Ha), medium potential area (1454,929 Ha), and low potential area (596,398 Ha).